Cycloplatinated(ii) complexes bearing an O, S-heterocyclic ligand: search for anticancer drugs. (12th April 2018) - Fereidoonnezhad, Masood; Ramezani, Zahra; Nikravesh, Mahshid; Zangeneh, Jalalaldin; Golbon Haghighi, Mohsen; Faghih, Zahra; Notash, Behrouz; Shahsavari, Hamid R.
Abstract : Cycloplatinated(ii ) complexes containing the 2-mercaptopyridine N -oxide ligand were synthesized and characterized spectroscopically. The biological activities of these complexes were also investigated. Abstract : 2-Mercaptopyridine N -oxide sodium salt (NaSpyO) was used as a bioactive ligand for the preparation of two new cycloplatinated(ii ) complexes. The reaction of the NaSpyO ligand with the cyclometalated platinum complexes [PtCl(C^N)(dmso)], 1, C^N = deprotonated form of 2-phenylpyridine (ppy, 1a ) or 7, 8-benzoquinoline (bzq, 1b ), afforded the complexes [Pt(C^N)(SpyO)], 2, C^N = ppy (2a ) or bzq (2b ). These complexes were characterized in solution via NMR spectroscopy. Single-crystal X-ray determination (in the case of2a ) and theoretical calculations confirmed that the SpyO ligand acted as a chelate (sulfur atom is cis to the carbon atom of the C^N ligand). The optical properties of both complexes were studied by UV-visible spectroscopy. The lower energy bands in2 had a mixed transition character ( 1 MLCT/ 1 LC/ 1 L′LCT, L = C^N and L′ = SpyO), and this assignment was supported by the time-dependent density functional theory (TD-DFT) calculations. The cytotoxic activities of2 were tested on five different human cancer cell lines: A549 (non-small cell lung cancer), MCF-7 (breast cancer), SKOV3 (ovarian cancer), MDA-MB-231 (breast cancer), and HT-29 (colon colorectal cancer). The effects of these compounds on the proliferation of the non-tumoral breast cell line (MCF-12A) showed good selectivity among the tumorigenic and non-tumorigenic cell lines. These complexes revealed good to moderate anti-proliferative activity. Electrophoresis mobility shift assays and molecular docking studies were also carried out on2 to determine the specific binding mode and the orientation of binding to DNA.